URINE ANALYSIS OF ETAWA BREED GOATS IN SUKAWATI DISTRICT, GIANYAR REGENCY BALI - Gusti Putu Arni Safitri; Anak Agung Sagung Kendran; Luh Gde Sri Surya Heryani; Ida Bagus Komang Ardana; I Nyoman Suarsana; Sri Kayati Widyastuti; Romy Muhammad Dary Mufa (Buletin Veteriner Udayana, 2024)
Etawa crossbreed goats (Capra aegagrus hircus) are livestock that are starting to be developed among breeders. In goat farming there are health problems that arise both clinically and subclinically, including disorders of the urinary tract. This study aims to determine the clinical condition of Etawa crossbreed goats (PE) in Sukawati District, Gianyar Regency by using urine examination. This study used 30 urine samples from Etawa crossbreed goats at the Raka Etawa Farm. A total of 10-30 ml of urine is taken using the mid-stream method and collected in a urine container which is then tested using a dipstick pad. This research is an observational study with a cross sectional study design using a purposive sampling method. Based on the results of the examination, data was obtained in the form of specific gravity (BJ) with a range of 1,005-1,010 and an average of 1.00567; pH in the range 8-9 and an average of 8.867; a total of 18 samples were found to contain proteins in the range 15-30 and an average of 15.83; and negative results were found in the parameters glucose, negative bilirubin, ketones, erythrocytes, urobilinogen, nitrites and leukocytes. These results indicate that the clinical condition of Etawa crossbreed goats (PE) is healthy (not sick) through urine examination in the form of physical examination and dipstick. It is necessary to carry out additional examinations in the form of examination of urine sidemen and bacterial culture, as well as measuring the specific gravity (BJ) using a refractometer to obtain a more accurate value.